UJI AKTIVITAS EKSTRAK ETANOL DAUN SINGKONG (Manihot utilissima Pohl) SEBAGAI LARVASIDA Aedes aegypti - ., Novi Ervina (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Dengue Haemorrhagic Fever is a very dangerous virusdisease because it can cause people die quickly (a few days). One of theefforts to overcome the disease is using larvacide. Cassava’s leaves(Manihot utilissima Pohl) contain saponins and flavonoids that havelarvacide activity. Objective. The purpose of this research is to know theactivity of cassava’s leaves ethanol extract as larvacide of Aedes aegypti,to know the compounds that contained in cassava’s leaves, to determineconcentration of cassava’s leaves ethanol extract which has larvacideactivity with LCand to analyze larvacide activity comparison betweencassava’s leaves ethanol extract and temephos. Methodology. 1125instar III/IV Aedes aegypti larvae were used for this experiment whichdivided into nine groups. The groups were one negative control group(aquades), one positif control group (temephos) and seven experimentalgroups with concentration of 0,5%, 1%, 1,5%, 2%, 2,5%, 3% and 3,5%.Each group consist of 25 larvae. Each experiment was replicated fivetimes. Mortality rate data was analyzed with One Way Anova Test andthen continued with Tukey Test. Probit Analysis was used to know thevalue of LC9090,. Results. Cassava’s leaves ethanol extract has larvacideactivity to Aedes aegypti with LCvalue at 2,613%. There is nosignificance difference of larvacide activity between cassava’s leavesethanol extract with concentration of 3% and 3,5% compared to temephos.Conclusion. Cassava’s leaves ethanol extract has larvacide activity toAedes aegypti.90Keywords: Ethanol extract, cassava’s leaves, larvacide, Aedes aegypti1)Medical School, Faculty of Medicine, University of Tanjungpura,Pontianak, West Borneo2)Pharmacy School, Faculty of Medicine, University of Tanjungpura,Pontianak, West Borneo3)Departement of Parasitology, Medical School, Faculty of Medicine,University of Tanjungpura, Pontianak, West Borneo